Exploring Grammatical Errors in English Abstracts: Insights from UMI Student Journals - Ratnawati, Ratnawati; Chuzaimah, Chuzaimah; Burhanuddin, Burhanuddin; Reza, Riri (ELT Worldwide: Journal of English Language Teaching, 2025)
This study investigates the grammatical errors present in English abstracts written by students at Universitas Muslim Indonesia (UMI), aiming to identify prevalent error types and uncover underlying factors influencing these lapses. Adopting a qualitative descriptive design, the researcher analyzed five English abstracts each from a different UMI faculty using Surface Structure Taxonomy (SST) to categorize errors into omission, addition, misformation, and misordering. Semi-structured interviews with the authors of the abstracts were also conducted to provide contextual insights into the causes of these errors. The findings reveal a total of 35 errors: 19 misformation errors, 8 omission errors, and 8 addition errors, with no instances of misordering. Misformation errors, particularly those involving incorrect verb forms, prepositions, and pluralization, emerged as the most frequent. Interview data point to several contributory factors, such as native language interference, limited mastery of formal writing rules, minimal use of grammar-checking tools, insufficient lecturer guidance, and the absence of clear faculty-level guidelines on English abstract composition. These results underscore the need for targeted pedagogical strategies. Recommendations include developing comprehensive writing guidelines, integrating technology-assisted proofreading tools, and offering formalized writing workshops that focus on discipline-specific conventions. By addressing both individual and systemic barriers, UMI and similar institutions can enhance students’ academic writing proficiency, thus improving the clarity, credibility, and global impact of their research outputs.